2013
DOI: 10.1177/000348941312200902
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Dioxide Laser Fiber for the Excision of Oral Leukoplakia

Abstract: The CO2 laser fiber did not show an advantage in operative time. The CO2 laser fiber did show better outcomes in the areas of blood loss, bipolar cautery use, and intraoperative margins needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 8 publications
2
2
0
Order By: Relevance
“…A similar study published by Chee and Sasaki also compared the use of cold steel and carbon dioxide laser for surgical resection of leukoplakia. They found no significant difference in their primary endpoints of resection time and blood loss 34 . These results were confirmed in our study.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…A similar study published by Chee and Sasaki also compared the use of cold steel and carbon dioxide laser for surgical resection of leukoplakia. They found no significant difference in their primary endpoints of resection time and blood loss 34 . These results were confirmed in our study.…”
Section: Discussionsupporting
confidence: 90%
“…They found no significant difference in their primary endpoints of resection time and blood loss. 34 These results were confirmed in our study. They reported no difference in postoperative pain between the groups.…”
Section: Discussionsupporting
confidence: 89%
“…With regards to complications following CO 2 laser treatment, in this study, pain and granuloma formation were observed. Pain is the most frequently reported complication (Chee & Sasaki, 2013; Deppe et al, 2012; Romeo et al, 2020; Tambuwala et al, 2014). Despite this, López‐Jornet and Camacho‐Alonso (2013) concluded that pain and swelling is more frequent when using a cold scalpel than when using CO 2 laser, and unlike our study, they did not observe granuloma formation.…”
Section: Discussionmentioning
confidence: 99%
“…5 In the treatment of leukoplakias with CO 2 laser, studies have shown recurrence rates ranging from 5.3% to 40.7% and malignant transformation rates ranging from 0 to 10.2%. [6][7][8][9] Thus, it presents a wide range of results.…”
Section: Introductionmentioning
confidence: 99%